2012
DOI: 10.2967/jnumed.111.099408
|View full text |Cite
|
Sign up to set email alerts
|

A Compartmental Model for Biokinetics and Dosimetry of18F-Choline in Prostate Cancer Patients

Abstract: PET with 18 F-choline ( 18 F-FCH) is used in the diagnosis of prostate cancer and its recurrences. In this work, biodistribution data from a recent study conducted at Skå ne University Hospital Malmö were used for the development of a biokinetic and dosimetric model. Methods: The biodistribution of 18 F-FCH was followed for 10 patients using PET up to 4 h after administration. Activity concentrations in blood and urine samples were also determined. A compartmental model structure was developed, and values of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…Six new patients were later included in the study. In these investigations, biodistribution and excretion data were collected for up to 4 h after injection of the radiopharmaceutical (Janzen et al., 2010; Giussani et al., 2012; Tavola et al., 2012). Previous human studies with 11 C- or 18 F-choline were limited up to 1 h after administration (Roivainen et al., 2000; DeGrado et al., 2002; Schmid et al., 2005; Kwee et al., 2006; Steiner et al., 2009; Sutinen et al, 2004). (C50) The biokinetics of 11 C-choline and 18 F-choline differ due to the different interactions of carbon and fluorine in the organism.…”
Section: C14 18f-cholinementioning
confidence: 99%
“…Six new patients were later included in the study. In these investigations, biodistribution and excretion data were collected for up to 4 h after injection of the radiopharmaceutical (Janzen et al., 2010; Giussani et al., 2012; Tavola et al., 2012). Previous human studies with 11 C- or 18 F-choline were limited up to 1 h after administration (Roivainen et al., 2000; DeGrado et al., 2002; Schmid et al., 2005; Kwee et al., 2006; Steiner et al., 2009; Sutinen et al, 2004). (C50) The biokinetics of 11 C-choline and 18 F-choline differ due to the different interactions of carbon and fluorine in the organism.…”
Section: C14 18f-cholinementioning
confidence: 99%
“…There is very limited data in the literature on the kinetics of FCH – all these studies include prostate cancer patients. Giussani et al 27 have developed a model of FCH kinetics based on biodistribution measurements that describes recirculation of radiopharmaceutical from major organs of early uptake (liver, spleen, kidneys) back into the blood pool, which may provide an explanation for late SUV increase in the parathyroid tissue. Tavola et al 28 concluded in their study that the simple linear model cannot adequately describe the kinetics of FCH, due to non-linear kinetics, which is associated with the release of FCH from the organs back into the blood.…”
Section: Discussionmentioning
confidence: 99%
“…The dosimetry of [ 18 F]-choline was estimated at 18 µSv/MBq (risk-weighted absorbed dose coefficient) [10] and 34.1 µSv/MBq (EDE) [11]. …”
Section: Reliability Of Dosimetry Estimatesmentioning
confidence: 99%